The Gaza Ceasefire Deal and The Trump Administration: Politics, Prospects, and Implications - Mukhtar Imam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
The Gaza ceasefire deal brokered during the Trump administration represents a critical moment in the ongoing Israeli-Palestinian conflict. This study examines the political dynamics, key stakeholders, and broader implications of the ceasefire, with a particular focus on the role of the U.S. government in facilitating the agreement. Using a qualitative approach with a library research method, this study analyzes various sources, including official documents, diplomatic reports, academic literature, and media publications. The research employs discourse analysis and content analysis to assess the motivations behind the ceasefire, its impact on regional stability, and its significance in shaping U.S. foreign policy. Findings indicate that the agreement, while providing temporary relief, does not resolve the fundamental political and territorial disputes driving the conflict. The study highlights the strategic interests of Israel, Hamas, Egypt, and Qatar, as well as the geopolitical considerations of the Trump administration in brokering the deal. This research contributes to a deeper understanding of the ceasefire’s long-term prospects and the broader challenges of achieving lasting peace in the Middle East. It underscores the complexities of U.S. involvement in the conflict and the ongoing struggle for Palestinian sovereignty. Future studies should explore the evolving role of international actors in mediating peace efforts and addressing the humanitarian crisis in Gaza.